Antiplasmodial activity of extracts of selected medicinal plants used by local communities in western Uganda for treatment of malaria - Katuura, Esther; Waako, Paul; Tabuti, John R. S.; Bukenya-Ziraba, Remigius; Ogwal -Okeng, Jasper (African Journal of Ecology, 2007)
This study investigated the antiplasmodial activity of ten medicinal plants used to treat malaria in Southwestern Uganda. The study plants were Bothlioclines longpipes (Olive and Hiern), N.E.Br., Toddalia asiatica (L.) Lam., Maesa lanceolata Forssk., Indigofera emerginella steud. Ex A. Rich., Lantana trifolia L., Vernonia lasiopus O. Hoffm., Trimmeria bakeri Gilg., Rhus natalensis Bernh. ex. Krauss Erythrophleum pyrifolia and Conyza sp. Dry powdered plant material was extracted by sequential cold maceration using petroleum ether, chloroform and ethanol solvents respectively. Extracts were subjected to in vitro antiplasmodial screening against wild strains of Plasmodium falciparum using the nitro-tetrazolium blue-based lactate dehydrogenase assay. The chloroform extract of M. lanceolata (EC50 1.60 μg ml−1.), showed the highest antiplasmodial activity followed by R. natalensis (EC50 1.80 μg ml−1). Other extracts with significant activity were the chloroform leaf extract of Bothriocline longipes (EC50 3.66 μg ml−1) and the petroleum ether root extract of T. bakeri (EC50 3.955 μg ml−1).
Keywords: Antimalarial; Plasmodium falciparum; Traditional medicine; Uganda